Numerical Modelling of Tailings Dam Thermal-Seepage Regime Considering Phase Transitions. (1st August 2017) - Alekseevich, Aniskin Nikolay; Sergeevich, Antonov Anton
Abstract : Statement of the Problem . The article describes the problem of combined thermal-seepage regime for earth dams and those operated in the permafrost conditions. This problem can be solved using the finite elements method based on the local variational formulation. Results . A thermal-seepage regime numerical model has been developed for the "dam-foundation" system in terms of the tailings dam. The effect of heat-and-mass transfer and liquid phase transition in soil interstices on the dam state is estimated. The study with subsequent consideration of these factors has been undertaken. Conclusions . The results of studying the temperature-filtration conditions of the structure based on the factors of heat-and-mass transfer and liquid phase transition have shown that the calculation results comply with the field data. Ignoring these factors or one of them distorts the real situation of the dam thermal-seepage conditions.